Study on Virtual Screening of Treated Pistachio vera Shell Powder as a Potential Sorbent in Sequestering Ubiquitous Divalent Metal Ions from Aqueous Matrices - N. Muthulakshmi Andal; N. Shyamala Devi; K. Vivithabharathi (Challenges and Advances in Chemical Science Vol. 3, 2021)
Water pollution due to noxious heavy metals such as Hg(II), Cr(VI), Cd(II) and Pb(II) ions etc., has been tremendously gaining attention. Increasing concentrations of these metals into the ecosystem constitute a severe health hazard due to their toxicity, accumulation and bio- magnification. Lead contamination of drinking water is a great threat via lead pipes, plating units etc. Pistachio vera shell (PVS) is a hard layer surrounding the nut kernels. The current work evaluates the feasibility of powdered Pistachio vera shell (PVSP) - a bio waste in sequestering Pb(II) ions after treating with 0.1N HCl / NaOH to enhance its sorption efficacy (TPVSP). SEM, FTIR and microscopic analyses are recorded for material characterization. The competence of the sorbent material is experimentally verified through Batch mode under various operating factors viz., particle size and dosage of TPVSP, agitation time interval between TPVSP and Pb(II) ions, initial concentrations of Pb(II) ions, pH of the adsorption medium, effects of cations, anions, co-ions and influence of temperatures on Pb(II) – TPVSP system. The residual concentrations of Pb(II) ions from aqueous solutions are analyzed using Atomic Absorption Spectrophotometer (SHIMADZU-AA-6200). Langmuir and Freundlich models are applied to describe the adsorption capacity. Column studies are conducted to ensure the quantitative estimation of TPVSP, wherein 99% of Pb(II) is removed by 40 mg TPVSP at a flow rate of 100 ml/10 mins.